Sodium-ion battery negative electrode material and preparation method and application thereof
By pre-sodiumization treatment and chemical vapor deposition coating of the sodium ion battery anode material, the problem of low first efficiency of the sodium ion battery anode material in the prior art during the initial cycle is solved, and higher cycle stability and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202311417255.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The existing sodium ion battery anode materials have a large irreversible capacity during the initial cycle, resulting in low first efficiency and difficult to fundamentally solve their capacity loss problem during the initial cycle.
By dissolving sodium lignin sulfonate and the loaded material, spray drying, high-temperature decomposition and carbonization, chemical vapor deposition, etc., a pre-sodium core is prepared and coated through chemical vapor deposition to form a sodium ion battery negative electrode material.
Through pre-sodiumization treatment, this method improves the first effect of the negative electrode material of sodium ion battery, reduces irreversible capacity, and enhances the cycle stability and electrochemical performance of the battery.
Smart Images

Figure CN119898745A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery negative electrode materials, and in particular to a sodium ion battery negative electrode material and a preparation method and application thereof. Background Art
[0002] Sodium-ion battery is a secondary battery. Sodium and lithium belong to the alkali metal main group and have similar physical and chemical properties to lithium. Since the commercialization of rechargeable lithium-ion batteries, graphite carbon has been widely used as a reliable negative electrode material due to its high coulombic efficiency, excellent cycle stability and low cost. However, since the radius of sodium ions is larger than that of lithium ions, graphite carbon exhibits low specific capacity in sodium-ion negative electrodes.
[0003] The disorder of hard carbon provides pore adsorption sites in addition to intercalation, providing storage space for lithium and sodium ions, so it has attracted great interest as a negative electrode material for lithium or sodium ion batteries. In addition, compared with graphite, the large interplanar spacing induced by the inherent disordered microstructure of hard carbon enables rapid migration of lithium or sodium ions in the carbon skeleton, which also indicates that hard carbon may have a potential high charging rate.
[0004] Nevertheless, hard carbon still has some defects as anode materials, such as large hysteresis in the ion insertion / extraction process, low initial Coulombic efficiency, and poor electronic conductivity.
[0005] In order to expand the capacity advantage of hard carbon, a large number of micro / mesopores are introduced to increase the adsorption sites to improve the specific capacity, but this method increases the irreversible capacity due to the increase in specific surface area. In addition, hard carbon and other highly conductive materials are compounded or nanosized to improve their electronic conductivity and overall electrochemical performance, but these methods cannot fundamentally solve the problem of low first efficiency due to its large irreversible capacity during the initial cycle. If conventional modification methods such as carbon coating are used to reduce the active surface area of hard carbon, its initial irreversible capacity will be reduced. However, it is difficult to completely eliminate the large capacity loss during the first charge and discharge process by this method alone. Summary of the invention
[0006] The purpose of the present invention is to provide a sodium ion battery negative electrode material and a preparation method and application thereof in view of the defects of the prior art. The preparation method has a simple process and solves the low initial efficiency problem of the sodium ion battery negative electrode material by pre-sodium treatment of the negative electrode material.
[0007] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a negative electrode material for a sodium ion battery, the preparation method comprising:
[0008] Dissolving sodium lignin sulfonate and a loading material to obtain a mixed solution;
[0009] The mixed solution is spray-dried to obtain microsphere particles;
[0010] Under an inert atmosphere, the microsphere particles are placed in a rotary kiln for heating to carbonize the sodium lignin sulfonate and the support material, and the sodium lignin sulfonate is decomposed to obtain a pre-sodium core;
[0011] In the rotary kiln, the pre-sodiumized core is coated by chemical vapor deposition to obtain a negative electrode material for a sodium ion battery.
[0012] Preferably, the dissolving solvent is one or more of water, ethanol, toluene, xylene, N-methylpyrrolidone, dimethylformamide, acetonitrile or tetrahydrofuran.
[0013] Preferably, the mass ratio of the dissolved solute to the solvent is 1:10-1:2; wherein the mass ratio of the sodium lignin sulfonate to the support material is 1:8-10:1.
[0014] Preferably, the load material is any one or more of starch, resins, sugars, polyvinyl pyrrolidone, asphalt, carboxymethyl cellulose, polydopamine, tannic acid, polyethylene glycol, polyacrylonitrile or polyacrylic acid.
[0015] Preferably, the air inlet temperature of the spray drying is 80°C-300°C, and the air outlet temperature is 50°C-200°C.
[0016] Preferably, the heating temperature is 700° C.-1300° C., and the heating time is 1 hour-12 hours.
[0017] Preferably, the temperature of the chemical vapor deposition is 400° C.-1000° C., and the time is 1 hour-12 hours.
[0018] In a second aspect, the present invention provides a negative electrode material for a sodium ion battery, characterized in that the negative electrode material for a sodium ion battery is prepared by any preparation method described in the first aspect above.
[0019] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the sodium ion battery negative electrode material described in the second aspect.
[0020] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode sheet described in the third aspect.
[0021] The preparation method of the negative electrode material of a sodium ion battery provided in an embodiment of the present invention achieves the effect of pre-sodiumization through spray drying, high temperature decomposition and carbonization, chemical vapor deposition and other processes, wherein the high temperature decomposition and carbonization and chemical vapor deposition are all carried out in a rotary kiln, thereby achieving the continuity of the preparation process, simplifying the process flow, and facilitating large-scale production. The carbonization process can form a pore structure between the load material and sodium lignin sulfonate, and the decomposition process can convert the ash component of the sodium lignin sulfonate into a pre-sodium component, generating a highly active Na 2 O or Na or Na 2 O 2 , forming a pre-sodium core. This can replenish sodium ions, increase the sodium content in the battery system, reduce the consumption of electrolyte, and make up for the consumption of sodium ions in the formation process of the solid electrolyte interface film. The pore structure is closed by chemical vapor deposition to protect the highly active Na 2 O or Na or Na 2 O 2 , which enhances the pre-sodium effect, while reducing the specific surface area, reducing the formation of SE I film, and improving the first effect problem of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A flow chart of a method for preparing a negative electrode material for a sodium ion battery provided in an embodiment of the present invention;
[0023] Figure 2 The charge and discharge curves of button-type half-cells assembled in Examples 1-8 of the present invention and Comparative Example 1;
[0024] Figure 3 The first effect data statistics of button-type half-cells assembled in Examples 1-8 of the present invention and Comparative Example 1 are shown;
[0025] Figure 4 This is a graph of the cycle capacity retention rate of button-type half-cells assembled in Examples 1-8 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0028] The present invention provides a method for preparing a negative electrode material for a sodium ion battery, the process of which is as follows: Figure 1 As shown, the following steps are included:
[0029] Step 110, dissolving sodium lignin sulfonate and a load material to obtain a mixed solution;
[0030] Specifically, the load material can be any one or more of starch, resins, sugars, polyvinyl pyrrolidone, asphalt, carboxymethyl cellulose, polydopamine, tannic acid, polyethylene glycol, polyacrylonitrile or polyacrylic acid. The dissolved solvent is one or more of water, ethanol, toluene, xylene, N-methylpyrrolidone, dimethylformamide, acetonitrile or tetrahydrofuran, preferably ethanol or water. The mass ratio of solute to solvent can be specifically 1:10-1:2, preferably 1:6-1:3. Among them, the mass ratio of sodium lignin sulfonate to load material is 1:8-10:1, preferably 1:4-5:1.
[0031] Here, sodium lignin sulfonate serves as both a carbon source and a pre-sodium precursor, which makes the pre-sodium effect of the product obtained by subsequent pre-sodiumization better.
[0032] Step 120, spray drying the mixed solution to obtain microsphere particles;
[0033] Specifically, the spray drying can be carried out in a spray drying apparatus, and the air inlet temperature of the spray drying can be 80°C-300°C, preferably 100°C-280°C. The air outlet temperature can be 50°C-200°C, preferably 80°C-180°C.
[0034] Step 130, in an inert atmosphere, the microsphere particles are placed in a rotary kiln for heating to carbonize the sodium lignin sulfonate and the support material, and the sodium lignin sulfonate is decomposed to obtain a pre-sodium core;
[0035] Specifically, the inert atmosphere can be one or more of nitrogen, argon or helium. The heating temperature is specifically 700° C.-1300° C., preferably 800° C.-1200° C. The heating time can specifically be 1 hour-12 hours, preferably 3 hours-9 hours.
[0036] In this step, sodium lignin sulfonate (C 20 H 24 Na 2 O 10 S 2 ) Pyrolysis will produce C, H 2 S, alkanes (such as methane, ethane), coke, Na 2 CO 3 Etc. Among them, Na 2 CO 3 It can be understood as an intermediate product, Na2 CO 3 Decomposed by heat, after high temperature treatment, the ash component of sodium lignin sulfonate can be converted into pre-sodium component, that is, sodium lignin sulfonate is converted into pre-sodium precursor, which solves the low capacity problem caused by high ash content of sodium lignin sulfonate, and the carbonization process. The carbonization process can also form a pore structure between sodium lignin sulfonate and the load material, and the pore structure can accommodate the highly active sodium element or sodium oxide or sodium peroxide after decomposition. This step performs carbonization and pre-sodiumization simultaneously, simplifies the process flow, and can achieve a very good pre-sodium effect.
[0037] The specific chemical reaction equation is as follows:
[0038] Na 2 CO 3 =Na 2 O+CO 2 (1)
[0039] 2Na 2 O=2Na+Na 2 O 2 (2)
[0040] Step 140, in a rotary kiln, coating the pre-sodiumized core by chemical vapor deposition to obtain a negative electrode material for a sodium ion battery.
[0041] Specifically, the gas for chemical vapor deposition may include a carbon source gas and a shielding gas. The volume ratio of the carbon source gas to the shielding gas is 1:5-5:1, preferably 1:4-2:1. The carbon source gas may be one or more of methane, acetylene, ethylene, propylene or carbon monoxide. The gas flow rate when the carbon source gas is introduced may specifically be 0.1L / min-1.0L / min, preferably 0.8L / min. The shielding gas may be one or more of nitrogen, helium or argon. The gas flow rate when the shielding gas is introduced may specifically be 0.1L / min-1L / min, preferably 0.2L / min. The temperature of chemical vapor deposition is specifically 400°C-1000°C, preferably 500°C-900°C. The time is specifically 1 hour-12 hours, preferably 3 hours-9 hours.
[0042] Chemical vapor deposition coats the pre-sodium core to form a closed-pore structure, protecting the highly active Na 2 O or Na or Na 2 O 2 , forming a core-shell structure, which enhances the pre-sodium effect, while reducing the specific surface area and reducing the formation of SE I film.
[0043] The preparation method of the negative electrode material of a sodium ion battery provided in an embodiment of the present invention achieves the effect of pre-sodiumization through spray drying, high temperature decomposition and carbonization, chemical vapor deposition and other processes, wherein the high temperature decomposition and carbonization and chemical vapor deposition are all carried out in a rotary kiln, thereby achieving the continuity of the preparation process, simplifying the process flow, and facilitating large-scale production. The carbonization process can form a pore structure between the load material and sodium lignin sulfonate, and the decomposition process can convert the ash component of the sodium lignin sulfonate into a pre-sodium component, generating a highly active Na 2 O or Na or Na 2 O 2 , forming a pre-sodium core. This can replenish sodium ions, increase the sodium content in the battery system, reduce the consumption of electrolyte, and make up for the consumption of sodium ions in the formation process of the solid electrolyte interface film. The pore structure is closed by chemical vapor deposition to protect the highly active Na 2 O or Na or Na 2 O 2 , which enhances the pre-sodium effect, while reducing the specific surface area, reducing the formation of SE I film, and improving the first effect problem of the material.
[0044] The sodium ion battery negative electrode material provided by the embodiment of the present invention can be applied to the electrode material of the sodium ion battery.
[0045] In order to better understand the technical solution provided by the present invention, the following uses a number of specific examples to illustrate the specific process of preparing a negative electrode material for a sodium ion battery using the method provided by the above embodiment of the present invention, as well as the electrochemical properties of the prepared negative electrode material for a sodium ion battery.
[0046] Example 1
[0047] In the first step, 10 g of sodium lignin sulfonate and 40 g of starch are weighed according to a mass ratio of sodium lignin sulfonate to starch of 1:4, and then dissolved in 200 g of water according to a mass ratio of solute to solvent of 1:4 to obtain a mixed solution.
[0048] In the second step, the mixed solution is input into a spray dryer for spray drying to obtain microsphere particles. The temperature of the air inlet is 85°C and the temperature of the air outlet is 165°C.
[0049] The third step is to place the microsphere particles in a rotary kiln under a nitrogen atmosphere, heat the rotary kiln to 800°C, and keep it warm for 6 hours to carbonize the sodium lignin sulfonate and starch, and decompose the sodium lignin sulfonate to obtain a pre-sodium core.
[0050] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:4. The temperature is kept at 600°C for 3 hours, and the pre-sodiumized core is coated by chemical vapor deposition to obtain the negative electrode material of the sodium ion battery.
[0051] Afterwards, the prepared sodium ion battery negative electrode material was used as the negative electrode plate of the sodium ion battery, and a button half-cell was assembled for testing, as follows:
[0052] First, add 0.375g of carboxymethyl cellulose (CMC) to 15g of deionized water for dispersion, the dispersion disk speed is 2000r / min, the time is 30min, and a clear glue solution is obtained. Add 0.3g of conductive carbon black (SP) to the glue solution and continue to disperse, the dispersion disk speed is 2000r / min, the time is 40min, and a slurry is obtained. Add 14.175g of the prepared sodium ion battery negative electrode material to the slurry and continue to disperse, the dispersion disk speed is 2000r / min, the time is 40min, and then add an appropriate amount of water to adjust the viscosity to 2500mPa.s. Then add 0.375g of styrene butadiene rubber (SBR) emulsion (solid content is 40%) to the slurry, the dispersion disk speed is 1000r / min, and the time is 30min. Then reduce the dispersion disk speed to 500r / min, stir slowly for 30min, and take out the slurry. The slurry was coated on an aluminum foil current collector and dried in a vacuum oven at 80° C. for 12 hours. The dried electrode was cut to serve as the negative electrode of the sodium ion battery.
[0053] Then, the button-type sodium ion half-cell is assembled using the negative electrode sheet. The aqueous electrolyte of the button-type sodium ion half-cell is 1 mol / L sodium hexafluorophosphate (NaPF 6 ), the solvent of the electrolyte is dimethyl ether (DME). The counter electrode is a sodium sheet.
[0054] Finally, electrochemical tests were performed to evaluate the electrochemical performance. The test conditions were: charge cut-off voltage was 2V, discharge cut-off voltage was 0V, current density was 0.1C, and cycle test was performed for 300 cycles.
[0055] Example 2
[0056] In the first step, 50 g of sodium lignin sulfonate and 10 g of starch were weighed in a mass ratio of 5:1, and then dissolved in 240 g of water in a mass ratio of solute to solvent of 1:4 to obtain a mixed solution.
[0057] The remaining steps and the assembly and testing of the button-type half-cell are the same as those in Example 1.
[0058] Example 3
[0059] In the first step, 10 g of sodium lignin sulfonate and 40 g of starch were weighed in a mass ratio of 1:4, and then dissolved in 240 g of water in a mass ratio of 1:6 between the solute and the solvent to obtain a mixed solution.
[0060] The remaining steps and the assembly and testing of the button-type half-cell are the same as those in Example 1.
[0061] Example 4
[0062] The first and second steps are the same as in Example 1.
[0063] The third step is to place the microsphere particles in a rotary kiln under a nitrogen atmosphere, heat the rotary kiln to 1200°C, and keep it warm for 3 hours to carbonize the sodium lignin sulfonate and starch, and decompose the sodium lignin sulfonate to obtain a pre-sodium core.
[0064] The remaining steps and the assembly and testing of the button-type half-cell are the same as those in Example 1.
[0065] Example 5
[0066] The first, second and third steps are the same as in Example 1.
[0067] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:4. The temperature is kept at 1000°C for 1 hour, and the pre-sodiumized inner core is coated by chemical vapor deposition to obtain a negative electrode material for a sodium ion battery.
[0068] The assembly and testing of button-type half-cells are the same as in Example 1.
[0069] Example 6
[0070] The first, second and third steps are the same as in Example 1.
[0071] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and acetylene is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to acetylene of 1:4. The temperature is kept at 600°C for 3 hours, and the pre-sodiumized inner core is coated by chemical vapor deposition to obtain a negative electrode material for a sodium ion battery.
[0072] The remaining steps and the assembly and testing of the button-type half-cell are the same as those in Example 1.
[0073] Example 7
[0074] The first, second and third steps are the same as in Example 1.
[0075] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.4 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:2. The temperature is kept at 600°C for 6 hours, and the pre-sodiumized inner core is coated by chemical vapor deposition to obtain the negative electrode material of the sodium ion battery.
[0076] The assembly and testing of button-type half-cells are the same as in Example 1.
[0077] Example 8
[0078] The first, second and third steps are the same as in Example 1.
[0079] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:4. The temperature is kept at 600°C for 9 hours, and the pre-sodiumized inner core is coated by chemical vapor deposition to obtain the negative electrode material of the sodium ion battery.
[0080] The assembly and testing of button-type half-cells are the same as in Example 1.
[0081] Comparative Example 1
[0082] In the first step, 10 g of starch was weighed and dissolved in 40 g of water at a mass ratio of solute to solvent of 1:4 to obtain a mixed solution.
[0083] In the second step, the mixed solution is input into a spray dryer for spray drying to obtain microsphere particles. The temperature of the air inlet is 85°C and the temperature of the air outlet is 165°C.
[0084] The third step is to place the microsphere particles in a rotary kiln under a nitrogen atmosphere, heat the rotary kiln to 800°C, and keep the temperature for 6 hours to carbonize the starch, thereby obtaining carbonized particles.
[0085] In the fourth step, nitrogen is continuously introduced into the rotary kiln at a gas flow rate of 0.2 L / min and methane is introduced at a gas flow rate of 0.8 L / min according to a volume ratio of nitrogen to methane of 1:4. The temperature is kept at 600°C for 3 hours, and the carbonized particles are coated by chemical vapor deposition to obtain a sodium ion battery negative electrode material without pre-sodium.
[0086] according to Figure 2 It can be seen that the charge and discharge curves of the material prepared by the present invention are not abnormal compared with those of Comparative Example 1, indicating that the preparation method does not produce other side reactions.
[0087] according to Figure 3As shown, the first efficiency of Comparative Example 1 is only 82.84%. This is because the sodium ion battery negative electrode material obtained by the preparation method of the present invention successfully achieves the pre-sodium effect, improving the low first efficiency problem of the sodium ion battery negative electrode material. However, Comparative Example 1 lacks sodium source sodium lignin sulfonate, so the sodium ion battery negative electrode material prepared is not pre-sodium, so the first efficiency of the button half-battery assembled with this material is low.
[0088] Figure 4 As shown, the capacity retention rate of the button half-cell assembled in Comparative Example 1 decreases significantly after 75 cycles, while the capacity retention rate of the button half-cell assembled in the present application remains at a relatively high level after 300 cycles. This is because the pre-sodium supplementation of sodium in the battery system can effectively alleviate the consumption of sodium in the system caused by the reorganization of the SE I membrane during the cycle, and the preparation method of the present invention, i.e. the product of the pre-sodium process, has no negative impact on the battery performance, so the battery cycle stability is high.
[0089] Example 9
[0090] In the first step, 10 g of sodium lignin sulfonate and 80 g of asphalt are weighed in a mass ratio of 1:8, and then dissolved in 900 g of ethanol in a mass ratio of 1:10 to obtain a mixed solution.
[0091] In the second step, the mixed solution is input into a spray dryer for spray drying to obtain microsphere particles. The temperature of the air inlet is 100°C and the temperature of the air outlet is 80°C.
[0092] The third step is to place the microsphere particles in a rotary kiln under an argon atmosphere, heat the rotary kiln to 900°C, and keep it warm for 10 hours to carbonize the sodium lignin sulfonate and asphalt, and decompose the sodium lignin sulfonate to obtain a pre-sodium core.
[0093] In the fourth step, argon is continued to be introduced into the rotary kiln at a gas flow rate of 0.2 L / min and ethylene is introduced at a gas flow rate of 1 L / min according to a volume ratio of argon to ethylene of 1:5. The temperature is kept at 500°C for 12 hours, and the pre-sodiumized core is coated by chemical vapor deposition to obtain a negative electrode material for a sodium ion battery.
[0094] Example 10
[0095] In the first step, 10 g of sodium lignin sulfonate and 1 g of polyethylene glycol are weighed in a mass ratio of 10:1, and then dissolved in 22 g of acetonitrile in a mass ratio of 1:2 to obtain a mixed solution.
[0096] In the second step, the mixed solution is input into a spray dryer for spray drying to obtain microsphere particles. The temperature of the air inlet is 280°C and the temperature of the air outlet is 200°C.
[0097] The third step is to place the microsphere particles in a rotary kiln under an argon atmosphere, heat the rotary kiln to 1300°C, and keep it warm for 3 hours to carbonize the sodium lignin sulfonate and polyethylene glycol, and decompose the sodium lignin sulfonate to obtain a pre-sodium core.
[0098] In the fourth step, argon is continued to be introduced into the rotary kiln at a gas flow rate of 1 L / min and propylene is introduced at a gas flow rate of 0.2 L / min according to a volume ratio of argon to propylene of 5:1. The temperature is kept at 700°C for 6 hours, and the pre-sodiumized core is coated by chemical vapor deposition to obtain the negative electrode material of the sodium ion battery.
[0099] Embodiment 11
[0100] In the first step, 60 g of sodium lignin sulfonate and 10 g of polyacrylic acid were weighed in a mass ratio of 6:1, and then dissolved in 210 g of toluene in a mass ratio of solute to solvent of 1:3 to obtain a mixed solution.
[0101] In the second step, the mixed solution is input into a spray dryer for spray drying to obtain microsphere particles. The temperature of the air inlet is 160°C and the temperature of the air outlet is 50°C.
[0102] The third step is to place the microsphere particles in a rotary kiln under a helium atmosphere, heat the rotary kiln to 700°C, and keep it warm for 12 hours to carbonize the sodium lignin sulfonate and polyacrylic acid, and decompose the sodium lignin sulfonate to obtain a pre-sodium core.
[0103] In the fourth step, helium is continued to be introduced into the rotary kiln at a gas flow rate of 0.2 L / min and carbon monoxide is introduced at a gas flow rate of 0.6 L / min according to a volume ratio of helium to carbon monoxide of 1:3. The temperature is kept at 400°C for 12 hours, and the pre-sodiumized inner core is coated by chemical vapor deposition to obtain the negative electrode material of the sodium ion battery.
[0104] Example 12
[0105] In the first step, 10 g of sodium lignin sulfonate and 20 g of carboxymethyl cellulose were weighed in a mass ratio of 1:2, and then dissolved in 240 g of xylene in a mass ratio of 1:8 to obtain a mixed solution.
[0106] In the second step, the mixed solution is input into a spray dryer for spray drying to obtain microsphere particles. The temperature of the air inlet is 300°C and the temperature of the air outlet is 160°C.
[0107] The third step is to place the microsphere particles in a rotary kiln under a helium atmosphere, heat the rotary kiln to 1000°C, and keep it warm for 5 hours to carbonize the sodium lignin sulfonate and carboxymethyl cellulose, and decompose the sodium lignin sulfonate to obtain a pre-sodium core.
[0108] In the fourth step, helium is continued to be introduced into the rotary kiln at a gas flow rate of 0.6 L / min and carbon monoxide is introduced at a gas flow rate of 0.2 L / min according to a volume ratio of helium to carbon monoxide of 3:1. The temperature is kept at 800°C for 5 hours, and the pre-sodiumized inner core is coated by chemical vapor deposition to obtain the negative electrode material of the sodium ion battery.
[0109] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The preparation method comprises: Dissolving sodium lignin sulfonate and a loading material to obtain a mixed solution; The mixed solution is spray-dried to obtain microsphere particles; Under an inert atmosphere, the microsphere particles are placed in a rotary kiln for heating to carbonize the sodium lignin sulfonate and the support material, and the sodium lignin sulfonate is decomposed to obtain a pre-sodium core; In the rotary kiln, the pre-sodiumized core is coated by chemical vapor deposition to obtain a negative electrode material for a sodium ion battery.
2. The preparation method according to claim 1, characterized in that: The dissolving solvent is one or more of water, ethanol, toluene, xylene, N-methylpyrrolidone, dimethylformamide, acetonitrile or tetrahydrofuran.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the dissolved solute to the solvent is 1:10-1:2; wherein the mass ratio of the sodium lignin sulfonate to the load material is 1:8-10:
1.
4. The preparation method according to claim 1, characterized in that: The load material is any one or more of starch, resins, sugars, polyvinyl pyrrolidone, asphalt, carboxymethyl cellulose, polydopamine, tannic acid, polyethylene glycol, polyacrylonitrile or polyacrylic acid.
5. The preparation method according to claim 1, characterized in that: The air inlet temperature of the spray drying is 80°C-300°C, and the air outlet temperature is 50°C-200°C.
6. The preparation method according to claim 1, characterized in that: The heating temperature is 700° C.-1300° C., and the heating time is 1 hour-12 hours.
7. The preparation method according to claim 1, characterized in that: The temperature of the chemical vapor deposition is 400° C.-1000° C., and the time is 1 hour-12 hours.
8. A negative electrode material for a sodium ion battery, characterized in that: The sodium ion battery negative electrode material is prepared by the preparation method described in any one of claims 1 to 7 above.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the sodium ion battery negative electrode material according to claim 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Lignin based hard carbon microsphere as well as preparation method and application thereof
CN108217623A
Sodium-ion battery negative electrode material, preparation method thereof and sodium-ion battery
CN112047325A
High-first-effect hard carbon negative electrode for sodium ion battery
CN115417398A
High-capacity compact hard carbon negative electrode material and preparation method and application thereof
CN116722139A
Sodium-ion battery, and preparation method therefor and use thereof
WO2023186165A1